To solve the system of equations, we can use the method of substitution or elimination.
Let's use the method of elimination to solve the system.
We can start by multiplying the second equation by 2 to make the coefficients of x's match:
2(2x-4y) = 2(-16)
4x - 8y = -32
Now we have two equations in standard form:
2x + 8y = 8
4x - 8y = -32
Adding the two equations eliminates the y terms:
4x + 2x = -24
6x = -24
x = -4
Substituting the value of x back into one of the original equations:
2(-4) + 8y = 8
-8 + 8y = 8
8y = 16
y = 2
So the solution to the system of equations is x = -4 and y = 2.
Solve the system of equations. 2x+8y=8 2x−4y=−16 (1 point)
7 answers
Solve the system of equations. 7x+3y=−25 −7x+9y=−47
To solve the system of equations, we can use the method of elimination.
Let's start by multiplying the first equation by -1:
-1(7x + 3y) = -1(-25)
-7x - 3y = 25
Now we have two equations in standard form:
-7x - 3y = 25
-7x + 9y = -47
Adding the two equations eliminates the x terms:
(-7x - 3y) + (-7x + 9y) = 25 + (-47)
-14x + 6y = -22
Dividing both sides of the equation by -2:
(-14x + 6y) / -2 = -22 / -2
7x - 3y = 11
Now we have two equations:
7x - 3y = 11
-7x + 9y = -47
Adding the two equations eliminates the x terms:
(7x - 3y) + (-7x + 9y) = 11 + (-47)
6y = -36
y = -6
Substituting the value of y back into one of the original equations:
7x + 3(-6) = -25
7x - 18 = -25
7x = -25 + 18
7x = -7
x = -1
So the solution to the system of equations is x = -1 and y = -6.
Let's start by multiplying the first equation by -1:
-1(7x + 3y) = -1(-25)
-7x - 3y = 25
Now we have two equations in standard form:
-7x - 3y = 25
-7x + 9y = -47
Adding the two equations eliminates the x terms:
(-7x - 3y) + (-7x + 9y) = 25 + (-47)
-14x + 6y = -22
Dividing both sides of the equation by -2:
(-14x + 6y) / -2 = -22 / -2
7x - 3y = 11
Now we have two equations:
7x - 3y = 11
-7x + 9y = -47
Adding the two equations eliminates the x terms:
(7x - 3y) + (-7x + 9y) = 11 + (-47)
6y = -36
y = -6
Substituting the value of y back into one of the original equations:
7x + 3(-6) = -25
7x - 18 = -25
7x = -25 + 18
7x = -7
x = -1
So the solution to the system of equations is x = -1 and y = -6.
Solve the system of equations. –x+6y=13 4x–10y=–10 (1 point)
To solve the system of equations, we can use the method of substitution or elimination.
Let's use the method of substitution to solve the system.
From the first equation, we can isolate x:
-x + 6y = 13
x = 6y - 13
Now we can substitute this expression for x into the second equation:
4(6y - 13) - 10y = -10
24y - 52 - 10y = -10
14y - 52 = -10
14y = 42
y = 3
Substituting the value of y back into the expression for x:
x = 6(3) - 13
x = 18 - 13
x = 5
So the solution to the system of equations is x = 5 and y = 3.
Let's use the method of substitution to solve the system.
From the first equation, we can isolate x:
-x + 6y = 13
x = 6y - 13
Now we can substitute this expression for x into the second equation:
4(6y - 13) - 10y = -10
24y - 52 - 10y = -10
14y - 52 = -10
14y = 42
y = 3
Substituting the value of y back into the expression for x:
x = 6(3) - 13
x = 18 - 13
x = 5
So the solution to the system of equations is x = 5 and y = 3.
Solve the system of equations. 3x+6y=21 –5x+2y=13 (1 point)
To solve the system of equations, we can use the method of elimination.
Let's start by multiplying the first equation by 5 and the second equation by 3 to make the coefficients of x's match:
5(3x + 6y) = 5(21)
3(-5x + 2y) = 3(13)
which simplifies to:
15x + 30y = 105
-15x + 6y = 39
Adding the two equations eliminates the x terms:
(15x + 30y) + (-15x + 6y) = 105 + 39
36y = 144
y = 4
Substituting the value of y back into one of the original equations:
3x + 6(4) = 21
3x + 24 = 21
3x = -3
x = -1
So the solution to the system of equations is x = -1 and y = 4.
Let's start by multiplying the first equation by 5 and the second equation by 3 to make the coefficients of x's match:
5(3x + 6y) = 5(21)
3(-5x + 2y) = 3(13)
which simplifies to:
15x + 30y = 105
-15x + 6y = 39
Adding the two equations eliminates the x terms:
(15x + 30y) + (-15x + 6y) = 105 + 39
36y = 144
y = 4
Substituting the value of y back into one of the original equations:
3x + 6(4) = 21
3x + 24 = 21
3x = -3
x = -1
So the solution to the system of equations is x = -1 and y = 4.